2019
DOI: 10.1021/acs.analchem.9b00611
|View full text |Cite
|
Sign up to set email alerts
|

An Acoustic Trap for Bead Injection Attenuated Total Reflection Infrared Spectroscopy

Abstract: In this work, we introduce a system combining an acoustic trap for bead injection with attenuated total reflection (ATR) infrared (IR) spectroscopy. By mounting an acoustofluidic cell hosting an ultrasound source on top of a custom-built ATR fixture, we were able to trap beads labeled with the enzyme alkaline phosphatase without requiring any mechanical retention elements. Sequential injection analysis was employed for reproducible sample handling and bead injection into the acoustic trap. To showcase potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…To determine the source for this intriguingly reproducible deviation, the same ATR crystals and ATR fixture were used in the ATR setup built from commercial available optomechanics including xyz-stages and rotation mounts allowing for precisely adjusting the angle of incident, used in our previous studies. 8,10 From this experiment, we found that the d e,exp values for both crystals in combination with the 3-D printed liquid compartment exactly match the theoretically obtained values (absorbance for the Si ATR is given in Table 1). For this reason and due to the exact same deviation for both ATR materials, we assumed the small inaccuracies in dimension of the 3D-printed mirror mounts to result in a deviation of the angle of incidence, which highly affects the effective pathlength.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…To determine the source for this intriguingly reproducible deviation, the same ATR crystals and ATR fixture were used in the ATR setup built from commercial available optomechanics including xyz-stages and rotation mounts allowing for precisely adjusting the angle of incident, used in our previous studies. 8,10 From this experiment, we found that the d e,exp values for both crystals in combination with the 3-D printed liquid compartment exactly match the theoretically obtained values (absorbance for the Si ATR is given in Table 1). For this reason and due to the exact same deviation for both ATR materials, we assumed the small inaccuracies in dimension of the 3D-printed mirror mounts to result in a deviation of the angle of incidence, which highly affects the effective pathlength.…”
Section: Resultssupporting
confidence: 81%
“…3 These advantages of ATR spectroscopy have been exploited in a wide variety of fields including forensic science, 4 on-line monitoring 5 and biofilm studies. 6 Combination of ATR with novel high power IR light sources, 5,7 optimized liquid handling, 8,9 as well as divers modification of the ATR element indicates the potential of this technique. [10][11][12][13] Complementary to commercial, costly ATR prisms, crystals prepared from double-side polished Silicon wafer have emerged.…”
mentioning
confidence: 99%
“…Classic acoustic traps are mostly made of glass; 17,26 however, recent acoustofluidic devices based on aluminium have shown promising results for particle manipulation. 13,14,34 Thus, aluminium-based acoustic traps represent a low-cost alternative that can be easily manufactured in comparison to glassware. We took advantage of the thermal conductivity of aluminium to build a TE-controlled trap, which allowed us to perform our assay at the desired 37 °C and which further counteracted thermal drifts induced by the high gain of the piezo driving signal or environmental influences.…”
Section: Discussionmentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins research introduced an acoustic trap for bead injection combined with ATR-IR spectroscopy, 34 which has been used in a wide variety of applications due to its robustness. 32,33 Here, total reflection of the IR light within the ATR element generates an evanescent field that penetrates the sample on top of the ATR element to a depth of up to 2 µm.…”
Section: Introductionmentioning
confidence: 99%
“…These spectrometers are still considered as gold-standard for IR spectroscopy. The broad spectral coverage and robustness of FTIR spectrometers enabled applications in a variety of analytical tasks including quantitative analysis of liquids in off-line as well as in-line applications, [15][16][17][18][19][20] studying reactions at surfaces, [21][22][23] as well as clinical diagnositics. 24 An emerging, cost-effective alternative to FTIR spectrometers are filtometers that, in comparison with benchtop spectrometers, allow on-site measurements due to their small size and low energy consumption.…”
Section: Introductionmentioning
confidence: 99%